Analysis Determinants of Housewives to Control Saving Gold Behavior in Indonesian Sharia Pawnshops - Febtika Budiya Elsasari; Budi Sukardi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
Investment is something that must be done by someone to plan future needs. As a financial regulator in a family, investment is essential for housewives. Investments can be made in various instruments, one of which is by saving gold in Sharia Pawnshop. Gold savings at Sharia Pawnshop is a gold balance deposit service that can make it easier for people to invest in gold by saving money. Therefore, this study aims to determine the effect of attitudes, subjective norms, and behavioural control on their Interest in saving gold in Sharia Pawnshop. The methodology used in this research is quantitative with a purposive sampling technique. This study's primary data was obtained directly through the Sharia Pawnshop Unit Ngabean housewife customer. The data analysis technique used multiple linear regression. The data collection technique used a questionnaire distributed to 96 housewife customers in the Sharia Pawnshop Unit. The results showed that people's attitudes and behaviour control variables significantly affected the Interest in saving gold in Sharia pawnshops, while the subjective norm variable did not affect saving gold.